“Me, housekeeper”: reminiscences of slavery in domestic employment in Brazil - Silva, Bruna Gabriella Santiago (2021)
This article aims to analyze the context of vulnerability to which domestic workers are subjected in Brazil from a sociological-legal perspective about the written production Me, Maid – the modern slave quarters in the maid´s room (2019). We seek to bring approaches to the post-abolition period and how the reminiscences of slavery shape the dynamics of domestic work in Brazil. Bearing in mind that the most affected are black women, we seek to undertake an analysis based on the concept of intersectionality to reveal the vulnerability to which domestic workers are exposed within a perspective that highlights the intersections between race, class and gender.